Plasma proteomics in CML patients before and after initiation of tyrosine kinase inhibitor therapy reveals induced Th1 immunity and loss of angiogenic stimuli. (November 2016) - Söderlund, Stina; Christiansson, Lisa; Persson, Inger; Hjorth-Hansen, Henrik; Richter, Johan; Simonsson, Bengt; Mustjoki, Satu; Olsson-Strömberg, Ulla; Loskog, Angelica
Highlights: Plasma proteomics seems feasible and useful in CML patients. Protein patterns demonstrated a shift towards Th1-immunity after TKI treatment. Angiogenic factors were decreased after TKI treatment. Some single analytes were identified that could be of interest to study further in CML. Abstract: Background and aims: The simultaneous measurement of many proteins is now possible using multiplex assays. In this pilot study we investigated a total of 124 proteins in plasma from chronic myeloid leukemia (CML) patients with the purpose of identifying proteins that are differently expressed at diagnosis and after tyrosine kinase inhibitor (TKI) treatment initiation. Methods: Samples were taken from 14 CML patients at diagnosis and after three months of TKI treatment (imatinib or dasatinib). Samples were analyzed by Mesoscale Discovery, Myriad RBM MAP technology and Olink Proseek. Results: Multiple plasma proteins were differentially expressed before and after initiation of TKI therapy. Protein patterns demonstrated a possible shift towards Th1-immunity and reduced angiogenic stimuli. Further, some plasma proteins were identified that can be of potential interest to study further for biologic, prognostic or therapeutic significance such as E-selectin, uPAR, growth hormone and carbonic anhydrase IX. Conclusions: Plasma proteomics seems feasible and useful in CML patients, both for studying patterns of protein expression and for identifying single proteins differentially expressed before and after treatment. Plasma proteomics may be useful to map disease activity and biological processes. Hence, plasma proteomics can be used to understand drug mechanisms and treatment responses in CML.